La música polifónica flamenca del segle XV a les novel·les clàssiques catalanesTirant lo Blanc & Curial e Güelfa. - DE NIJS, BOB (Scripta, 2013)
There are specific references in Tirant lo Blanc and Curial e Güelfa to the probably direct knowledge that the authors had on Flemish polyphonic music, which came to the north of Italy during the first half of the fifteenth century and arrived in Naples.